EFEKTIVITAS KINERJA APARATUR DESA TERHADAP PERENCANAAN DANA DESA DI DESA SALO DUA KECAMATAN MAIWA KABUPATEN ENREKANG - Andiny, Arum Tri; Monalisa Ibrahim; Muhammad Ikbal (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
ABSTRACT Arum Tri Andiny, 2025. The Effectiveness of Village Apparatus Performance on Village Fund Planning in Salo Dua Village, Maiwa District, Enrekang Regency, (guided by Mrs. Monalisa Ibrahim and Mr. Muhammad Ikbal). This have a look at ambitions to decide the effectiveness of the overall performance of village equipment on village fund planning in Salo Dua Village and identify the factors that affect the planning. The research population amounted to 50 network leaders, with a saturated sampling technique, in which the whole population become sampled. This look at makes use of a descriptive quantitative technique with statistics series strategies through remark, questionnaires, and literature studies. facts evaluation became accomplished by using validity, reliability, and descriptive information checks the usage of IBM SPSS facts model 21.0. The results of the look at showed that the average overall performance variable of village apparatus turned into 61%, which became categorized as